Antecedents of consumer’s attitude towards social media influencer & its impact on purchase intention - Teo, Desmond De Wen (2019)
Social media influencers has become a popular form of marketing tool and are able to create a buzz to increase exposure for businesses and attract the public eyes. This study is designed to explore on the effectiveness of social media influencer, which are focused on the characteristics that are informativeness, entertainment, source credibility, source attractiveness and product matchup. The previous mentioned variables are directed upon consumer attitude towards the social media influencer, which would in the end affect on the consumer purchase intention. Quantitative sampling method with a data set of 300 respondents was analyzed to attain the result. The findings has shown that informativeness, entertainment provided, source credibility, source attractiveness and product matchup of the social media influencer possesses a significant relationship towards consumers’ attitude which in the end affects their purchase intention positively.